Ko te Whenua te Utu = Land is the price : essays on maori history, land and politics (Auckland University Press, 2014)
For more than half a century, Keith Sorrenson? one of New Zealand's leading historians and himself of mixed Maori and Pakeha descent? has dived deeper than anyone into the story of two peoples in New Zealand. In this new book, Sorrenson brings together his major writing from the last 56 years into a powerful whole? covering topics from the origins of Maori (and Pakeha ideas about those origins), through land purchases and the King Movement of the nineteenth century, and on to twentieth-century politics and the new history of the Waitangi Tribunal. Throughout his career, Sorrenson has b.